Implementasi Kepemimpinan Transformasional di Lembaga Pendidikan Islam - Ummiy Fauziyah Laily; Binti Maunah (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2022)
The purpose of this article is to discuss how transformational leadership is implemented in Islamic educational institutions. Transformational leadership has recently become a popular topic of discussion for application in Islamic educational institutions. A very large influence on the success or failure of transformational leadership in an educational institution will aid in the institution's advancement and growth, with the function of the principal motivating the institution's members and executing the leadership wheel effectively. Transformational leadership is attainable via idealized influence, inspirational motivation, and intellectual stimulation. This study makes use of a comprehensive literature review as its methodology (SLR). This study uses library research strategies to acquire data from diverse sources such as books, journals, articles, etc.